CYBERACTIVISM IN PALESTINIAN CONFLICT NEWS COMMENTS ON AL-JEZEERA YOUTUBE CHANNEL: A CYBERPRAGMATIC STUDY (AKTIVISME SIBER DALAM KOMENTAR BERITA KONFLIK PALESTINA DI KANAL YOUTUBE AL-JAZEERA: KAJIAN SIBERPRAGMATIK) - Yufni Faisol; Syofyan Hadi; Reflinaldi Reflinaldi; Wahyudi Rahmat (Universitas PGRI Sumatera Barat, 2021)
Youtube has become an online protest media that is used to trigger and escalate conflicts in various countries. This study explains illocutionary speech acts in the comments on the Palestinian conflict news on the Al-Jazeera Youtube channel. This type of qualitative research takes 5 news reports of the attack on the Al-Aqsa mosque complex by the Israeli military published on May 10, 2021, as data sources. Data were collected through internet archive documentation techniques and listening techniques without engaging in conversation. The data that has been classified on the data card was then analyzed by the matching method following the stages of qualitative analysis. The researchers found 720 illocutionary speech acts consisting of 4 types: representative, directive, expressive, and commissive. Representative speech acts were found in 25 utterances (4%), a directive in 320 utterances (44%), expressive in 282 utterances (39%), and commissive in 93 utterances (13%). From a function perspective, illocutionary utterances in the data source contain the functions of stating, inviting, pleading, demanding, condolence, anger, criticizing, promising, and threatening. The types and functions of illocutionary speech acts found were closely related to the context of the Israeli-Palestinian conflict. From these utterances, the speakers try to mobilize cyberactivism to generate public resistance against the Israeli occupation.